The Role of Schools in Spiritual Education and the Formation of Children’s Islamic Character - Brata, Andie Kusuma; Gusmian, Islah; Salman, Abdul Matin bin (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The phenomenon of moral degradation among junior high school students has shown an increasingly concerning trend. This study aims to examine the role of school management in implementing spiritual education to shape the Islamic character of junior high school students. A descriptive qualitative method was employed, with teachers and students at MTs N 1 Surakarta serving as the research subjects. Data were collected through document analysis, in-depth interviews, and observation. The findings reveal: (1) Planning emphasizes school-designed programs such as 3S (greeting, shaking hands, smiling), which are supported by standard operating procedures (SOPs) and clearly assigned responsibilities to ensure systematic implementation of spiritual education; (2) Organization involves a collaborative system among homeroom teachers, subject teachers, school counselors, and all educational staff, with particular emphasis on the role of the vice principal for student affairs in character development; (3) Implementation of spiritual education is carried out through the active participation of students, teachers, committees, and other institutions, with a focus on fostering good morals and manners through habituation; and (4) Control and evaluation are conducted by providing continuous guidance and socialization of school regulations to students to reinforce and sustain the positive habits that have been instilled.